2018
DOI: 10.2147/prbm.s178080
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of family environmental, behavioral, and social functional factors in children with attention-deficit/hyperactivity disorder

Abstract: BackgroundThe objective of this study was to investigate relationships among family environmental characteristics, behavior problems, and social function impairments in children with ADHD.MethodsAmong children from four primary schools in Shantou city of China, 132 who were diagnosed with ADHD were selected and 138 typically developing children were recruited from the same schools. These children were evaluated using the self-designed questionnaire, FES-CV, CPRS, CTRS, and WFIRS-P for familial environment, beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Family characteristics have a profound impact on the experiences and life trajectories of offspring, playing an important role in emotional and behavioral development during childhood ( 31 ). Thus, the family environment may be relevant for the course of various mental and psychological diseases and ultimately clinical outcomes, including major depressive disorder ( 32 ), trichotillomania, obsessive–compulsive disorder ( 33 ), and ADHD ( 23 ). Character profiles are correlated with individual differences in goals and values, which are based on learning and the perceptions of self and others ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Family characteristics have a profound impact on the experiences and life trajectories of offspring, playing an important role in emotional and behavioral development during childhood ( 31 ). Thus, the family environment may be relevant for the course of various mental and psychological diseases and ultimately clinical outcomes, including major depressive disorder ( 32 ), trichotillomania, obsessive–compulsive disorder ( 33 ), and ADHD ( 23 ). Character profiles are correlated with individual differences in goals and values, which are based on learning and the perceptions of self and others ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each item was answered as “Yes = 1” or “No = 2” by one of the parents who spent more time with family and became involved in more family affairs. The FES-CV has good validity and reliability in Chinese people and works well in evaluating different kinds of families and testing the family relationships and family environment in China ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with ADHD experienced worse family environment. Parents obtaining lower education levels may increase ADHD risk among children [17]. ADHD symptoms were found to be signi cantly associated with alcohol use, depression, suicidal behavior [8,18], internet misuse [19][20][21][22] and bipolar disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…ADHD is characterized by developmentally inappropriate symptoms of inattention and/or hyperactivity/impulsivity, symptom onset prior to age 12, and impairment in at least two settings (American Psychiatric Association, 2013). Research has consistently indicated that children and adolescents with ADHD often experience academic difficulties (e.g., Altszuler et al, 2017;Arnold et al, 2020;Kent et al, 2011), peer relationship/ social difficulties (e.g., Aduen et al, 2018;de Boo & Prins, 2007;McQuade & Hoza, 2008Mikami et al, 2007;Ros & Graziano, 2018), and increased levels of conflict with parents and family (e.g., Altszuler et al, 2017;Churchill et al, 2018;Haydicky et al, 2015;Huang et al, 2018;Johnston & Lee-Flynn, 2011). Given the potential for poor long-term outcomes for children with ADHD, effective evidence-based treatment is essential to ensure the best possible outcomes for this group.…”
mentioning
confidence: 99%